Analysis of Kerf Taper Angle in Abrasive Water Jet Cutting of Makrana White Marble - Gupta, Vishal; Garg, M. P.; Khanna, R.; Khanna, R. (Asian Journal of Engineering and Applied Technology, 2013)
Abrasive water jet cutting (AWJ) process is used to experimental investigations parameters on kerf taper angles of makrana white marble. Marble is having a wide application in domestic, commercial and industrial construction so there is a need to investigate the AWJ cutting of marble. Three different process parameters were undertaken for this study; water pressure, nozzle transverse speed and abrasive flow rate. Experiments were conducted in varying these parameters for the cutting of marble. The design philosophy of Taguchi was followed to conduct the experiments. Analysis of variance (ANOVA) was used to evaluate the data obtained to determine the major significant process factors statistically affecting the kerf taper angle. The results revealed that the nozzle transverse speed was the most significant factor affecting on the kerf taper angle.